Locke : liaison probable et liaison nécessaire - Éric Marquer (Astérion)
We would like to stress the importance of connection of ideas in Locke notion of “knowledge”, and to recall how the author of the Essay defines reason. Reason is not the faculty of syllogistical reasoning, but of examining connections between singular ideas. Connection and association are not in opposition for Locke as an objective link would be to a purely subjective link. Indeed, association is a normal activity for the mind even if it sometimes has pathological consequences. Moreover, probable connections are very important to knowledge and they are not necessarily based on objective reasons (e.g. moral certainty). Finally, the connection of ideas creates habits of mind, just like the association. Therefore we have to understand what characterizes the “good” habits of the mind. Under these conditions, Locke defines connection and association as two ways of thinking with a subtle difference between them: the individual who “knows” is not the one who avoids any association of ideas, but one whose activity of mind goes beyond it. For the reasonable man, association of ideas is not a prejudice that hinders rational activity.